Washing solution and centrifugation affect kinematics of cryopreserved boar semen - Areeg M. Almubarak; Woohyeon Kim; Nabeel H. Abdelbagi; Saddah E. Balla; Il-Jeoung Yu; Yubyeol Jeon (The Korean Society of Animal Reproduction and Biotechnology, 2021)
Cryopreservation is a widely-used efficient means of long-term sperm preservation. However, unlike other types of semen, cryopreserved boar semen has reduced fertility and the efforts continue to optimize post-thawing sperm recovery. In this study, we evaluated the effects of various washing solutions (Hulsen solution, labmade DPBS and commercial DPBS) on post-thawing porcine sperm kinematics (CASA system), viability (SYBR-14/PI) and acrosome integrity (PSA/FITC). We also examined the effect of washing-centrifugation on frozen-thawed semen kinematics. The results indicate that type of washing solution and post-thawing centrifugation alters parameters linked to sperm quality (total motility, progressive motility, viability and acrosome integrity). Significantly higher (p < 0.05) motility and progressive motility were obtained when cryopreserved semen was processed with Hulsen solution. The postthaw percentage of live and intact acrosomal sperm was significantly higher in group 1 (Hulsen solution) as compared to other groups. Following thawing-centrifugation, the results showed significantly higher motility and progressive motility in group 1 than other groups. However, the latter two DPBS groups did not differ statistically. Taken together, Frozen-thawed spermatozoa motility, acrosome integrity and viability can be affected by the type of washing solution used. Moreover, centrifugation of frozenthawed semen has an unfavorable effect on total motility and progressive motility.